Hubungan Antara Karakter Motivasi Belajar dengan Hasil Belajar Siswa - Bella Cantika Putri; Aldila, Febri Tia; Matondang, Maria Marisa (Integrated Science Education Journal, 2022)
Research Objectives: The purpose of this study was to identify the relationship between the character of learning motivation and student learning outcomes. The population of this study were students of class XII MIA SMA Negeri 1 Muaro Jambi. The sample of this study was determined by the total sampling technique, which was 90 students. Methodology: This research is a quantitative descriptive study with data collection techniques by distributing questionnaires and tests. Questionnaires were used to collect data on students' learning motivation and tests were used to determine learning outcomes. The data analysis technique used is Pearson correlation to see how the relationship between the character of students' motivation and the acquisition of learning outcomes. Main findings: From the results of data analysis, the Pearson correlation is 0.297, so the correlation is in the high category. Therefore, it can be concluded that the Character of Learning Motivation has a relationship with student learning outcomes. Novelty of the study: The novelty of this research is to examine the relationship between motivational characters and student learning outcomes